Corrigendum to ‘Multiple myeloma: EHA-ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up’: (Annals of Oncology (2021) 32(3) (309–322), (S0923753420431692), (10.1016/j.annonc.2020.11.014)) - Dimopoulos, M. A.; Moreau, P.; Terpos, E.; Mateos, M. V.; Zweegman, Sonja; Cook, G.; Delforge, M.; Hajek, Roman; Schjesvold, F.; Cavo, Michele; Goldschmidt, Hartmut; Facon, T.; et al. (Annals of Oncology, 2022)
The EHA Executive Office and ESMO Guidelines Committee would like to publish a correction to the article section entitled TREATMENT OF RELAPSED/REFRACTORY PATIENTS, Patients who have received one prior line of therapy and the footnote to Figure 3. Original text: Venetoclax is a selective Bcl-2 inhibitor that promotes MM cell apoptosis. The phase III BELLINI trial evaluated the combination of venetoclax with Vd (VenVd) compared with Vd among RRMM patients, who had received 1-3 prior lines of therapy and were PI-sensitive. A significant PFS benefit was reported with VenVd among patients with t(11;14) (HR 0.10; P = 0.003) and those with high BCL2 expression (HR 0.26; P < 0.001) but no OS difference was shown in this population. On the contrary, Vd was superior to VenVd in terms of OS among patients without t(11;14) and low BCL2 (HR 3.13; P = 0.019).67 Therefore, VenVd is an option only for patients with t(11;14) or high BCL2 levels who have failed lenalidomide and are sensitive to PI. VenVd is awaiting EMA approval. The authors have revised the text as follows: Venetoclax is a selective Bcl-2 inhibitor that promotes MM cell apoptosis. The phase III BELLINI trial evaluated the combination of venetoclax with Vd (VenVd) compared with Vd among RRMM patients, who had received 1-3 prior lines of therapy and were PI sensitive. A significant PFS benefit was reported with VenVd among patients with t(11;14) (HR = 0.11; P = 0.004) and those with high BCL2 gene expression (HR = 0.24; P < 0.0001) but no OS difference was shown in this population. On the contrary, Vd was superior to VenVd in terms of OS among patients without t(11;14) and low BCL2 gene expression (HR = 3.04; P = 0.022).67 Therefore, VenVd is an option only for patients with t(11;14) who have failed lenalidomide and are sensitive to PI. Prospective clinical trials are needed to confirm the BELLINI findings in patients with RRMM with high BCL2 gene expression. Furthermore, antibiotic prophylaxis is recommended for all patients receiving VenVd. Venetoclax is not currently licensed for treatment of MM. The authors have revised reference 67 with: 67. Kumar S, Harrison S, Cavo M, et al. Venetoclax or placebo in combination with bortezomib and dexamethasone in patients with relapsed or refractory multiple myeloma (BELLINI): a randomised, double-blind, multicentre, phase 3 trial. Lancet Oncol. 2020 (12):1630-1642. Figure 3. Original footnote b: b For patients with t(11;14) or high BCL2 levels. Revised footnote b: b For patients with t(11;14).
CRIS-Team Scopus Importer:2023-03-23